PHYSICAL PROPERTIES OF SBR COMPOUNDS FOR THE EFFECT OF DIPHENYL GUANIDINE AND GRAIN DIRECTION - Fauzi, S.N.R.; Mohamad, N.; Ab Maulod, H.E.; Abd Razak, J.; Soh, T. C.; Ahsan, Q. (Journal of Advanced Manufacturing Technology (JAMT), 2024)
This study investigates the processability and physical properties of styrene butadiene rubber (SBR) compounds, particularly focusing on the effect of additive and grain direction of the two-roll process. SBR composites were prepared at varying diphenyl guanidine (DPG) levels of 0.5 and 1.5 phr, and the compounds were cut according to the machine direction (MD) and transverse direction (TD) prior to vulcanization. A lower DPG amount (0.5 phr) in SBR compounds significantly improved cure rate index and torque difference compared to a higher DPG amount (1.5 phr). The physical properties revealed that SBR with lower DPG content outperformed SBR with higher DPG, particularly in the TD orientation. The findings were further supported by swell measurement, toluene uptake and SEM analyses to assess the crosslinking and morphology. The study enhances understanding of the relationship between chemical treatment and grain orientation on the physical performance of rubber composites. It offers valuable insights for improving manufacturing processes and product quality in the rubber industry.